(untitled) - Haase, R. (New York, 1990)
This book only covers the phenomenological side of non-equilibrium thermodynamics, and does not include the statistical foundations. Consequentially, people who are new to non-equilibrium thermodynamics might do well to use a more recent and modern book to learn from.
Keywords: Thermodynamics,Nhiệt động lực học